Anti-Muslim hate on the eastern shores of the Mediterranean: Lebanon, the Hijab, and modernity/coloniality. Issue 12 (26th September 2021) - Kassem, Ali
ABSTRACT: Informed by the theorization of the modernity/(de)coloniality studies collective, this paper thinks alongside hijabi women in Lebanon – a small Arab Mediterranean country – and their lived experiences in "mainstream Lebanese society". Drawing on six-months of qualitative fieldwork through in-depth interviews and focus groups with photo-elicitation, the paper documents and analyses lived experiences of discrimination, exclusion and erasure. Identifying dehumanization, civility and progress, and a present potent wider rejection of Islam in Lebanon, it argues for a framing of participant's shared experiences as anti-Muslim racism under modernity/coloniality and highlights the need to de-exceptionalize the region and the analytical tools mobilized to understand it.